2021
DOI: 10.1002/ece3.7655
|View full text |Cite
|
Sign up to set email alerts
|

Decline and fall: The causes of group failure in cooperatively breeding meerkats

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 68 publications
4
23
0
Order By: Relevance
“…7). This agrees with previous observations that TB is the main cause of failure of established groups 24 .…”
Section: Group Extinction Under Climate Changesupporting
confidence: 93%
See 2 more Smart Citations
“…7). This agrees with previous observations that TB is the main cause of failure of established groups 24 .…”
Section: Group Extinction Under Climate Changesupporting
confidence: 93%
“…TB is a terminal disease for meerkats, and in the later stages of infection (henceforth, clinical TB), adult meerkats commonly develop pronounced submandibular lymph node swellings which grow in size and eventually burst. Individuals then die within approximately six months, causing an additional 6 % deaths of the total adult population per year 24,25 . Outbreaks of TB are the main cause of extinctions of established groups; 63 % of groups that were monitored until failure (54 groups in total) failed due to TB, and this rate increased to 100 % in groups that had persisted for > 8 years and subsequently failed 24 .…”
Section: Recent Climate Change and Tuberculosis Outbreaks In Meerkatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most social mole-rat groups are nuclear families and females will not readily mate with their father or brothers (75). As a result, natal individuals typically lack access to unrelated mating partners and if either breeder dies, all group members may slowly disperse and groups may dissolve (21, 37, 54, 56, 61). The fact that females rarely inherit a breeding position might also explain why sex differences in dispersal timing are small in Damaraland mole-rats (this study, 68) compared to other cooperative breeders (11,57,76), and why males and females invest similarly in cooperative foraging behaviour (30,48,77), with neither sex standing to gain more from helping (11,15,76,78).…”
Section: Discussionmentioning
confidence: 99%
“…In some of the most well-studied obligate cooperative mammals, pairs of individuals without helpers usually fail to breed successfully (17,50,51). New groups typically form and successfully breed when coalitions of individuals disperse and settle together (52,53), when large groups fission into smaller, distinct breeding units (54)(55)(56)(57), or when a breeding territory including helpers is inherited by existing group members (58)(59)(60)(61). Similar patterns of group formation as in obligate cooperative mammals are seen in many eusocial insect societies (62)(63)(64)(65), and various studies have suggested that the fissioning of large groups may also be an important driver of new group formation in the social mole-rats (19,21,31,66).…”
Section: Introductionmentioning
confidence: 99%